EFL High School Students’ Ability in Comprehending Short Stories - Ika Paramitha Lantu (Sintuwu Maroso Journal of English Teaching, 2016)
The objective of this research was to describe tenth graders’ ability in comprehending short stories text in SMA Negeri 1 Lage. This research was qualitative in nature. The data were collected from observation and documents. The result of this research shows that students increased their scores of comprehending narrative short stories after three meetings. Some suggestions are proposed in this article for future inquiry.Keywords: reading comprehension, narrative text, short stories